MANAGEMENT INFORMATION SYSTEM IN THE ORGANIZATIONAL SECTION OF THE REGIONAL SECRETARIAT OF MALANG CITY - Nabila, Dinda Salwa; Wibisono, Rizal Haryo; Nur, Robi'atul Lailiyah; Hannah, Ardeta Ayu; Cahyani, Aisyah Princess (PERCIPIENCE International Journal of Social, Administration, & Entrepreneurship, 2024)
Based on the mandate of Law Number 25 of 2009 concerning Public Services, the government is required to improve the quality and guarantee of the implementation of public services in accordance with the general principles of government and provide protection for every citizen from abuse of authority in the provision of public services related to the basic needs of the community. In providing its services, the government is obliged to provide excellent service to the community, so as to achieve the desired goals. The problem that became the main focus in this research was regarding tools in formulating policies as is a function of the Organizational Section of the Regional Secretariat of Malang City. One of these tools is data which is then managed into a Management Information System. Based on this, the main discussion that will be raised in this study is about what are the factors in formulating policies and how the information needed by the Organizational Section of the Malang City Regional Secretariat as an assistant to carry out other functions.